CSC402 - Programming I / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course is an introduction to problem-solving using computers. It emphasizes various aspects of problem-solving, mainly consisting of the problem domain, phases of problem-solving and basic techniques in designing a solution. The approach to problem-solving is via top-down design and structured programming. The emphasis is on solving problems using a computer rather than the syntactical aspects of the chosen programming language.